2023
DOI: 10.1055/a-1990-0201
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia – Definition, Radiological Diagnosis, Clinical Significance

Abstract: Background Sarcopenia is an age-related syndrome characterized by a loss of muscle mass and strength. As a result, the independence of the elderly is reduced and the hospitalization rate and mortality increase. The onset of sarcopenia often begins in middle age due to an unbalanced diet or malnutrition in association with a lack of physical activity. This effect is intensified by concomitant diseases such as obesity or metabolic diseases including diabetes mellitus. Method With effective preventati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 89 publications
(253 reference statements)
0
8
0
1
Order By: Relevance
“…One approach involves improving the accuracy of CT-based biomarkers. For instance, this could be achieved through the quantification of sarcopenia, which may be an important attribute in capturing fracture risk in older individuals [ 95 , 96 ]. In the context of cancer patients, a study revealed that muscle attenuation was not significantly different between patients with and without fractures [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…One approach involves improving the accuracy of CT-based biomarkers. For instance, this could be achieved through the quantification of sarcopenia, which may be an important attribute in capturing fracture risk in older individuals [ 95 , 96 ]. In the context of cancer patients, a study revealed that muscle attenuation was not significantly different between patients with and without fractures [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bei Patienten mit onkologischen Erkrankungen wird die körperliche Leistungsfähigkeit erfasst, um die Risiken von Morbidität und Mortalität abzuschätzen. Die krankheitsassoziierte und oft unbewusste Reduktion des Körpergewichts bei der Kachexie [38] kann nicht immer von der im Alter scheinbar physiologischen Abnahme der Muskelmasse im Rahmen der Sarkopenie unterschieden werden [39][40][41][42].…”
Section: Parameter Der Body Compositionunclassified
“…The physical fitness is often assessed in patients with oncological diseases to evaluate the risks of morbidity and mortality. The disease-related and often unknowing weight loss in cachexia [38] cannot always be differentiated from the age-related physiological loss of muscle mass in sarcopenia [39][40][41][42].…”
Section: Body Composition Parametersmentioning
confidence: 99%
“…Sarcopenia is a progressive skeletal muscle disorder that causes adverse conditions such as functional loss, mortality and morbidity as a result of the decrease in skeletal muscle mass and strength [6]. Sarcopenia is considered a specific disease [7].…”
Section: What Is New? What Is Important?mentioning
confidence: 99%